Evaluasi pada Website Fakultas Peternakan Universitas Brawijaya menggunakan Usability Testing - Wheny Mela Sari; Aditya Rachmadi; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Faculty of Animal Science Universitas Brawijaya uses a website as a media service to facilitate the work of the campus. Based on the results of interviews and observations, problems were found on the website of the Faculty of Animal Science, namely there were user complaints about the appearance of the website and its functions (icons and links) and some menus could not be used as expected by users, from these deficiencies related to usability problems. Evaluation was conducted to determine the level of usability of the website using the usability testing method and using the system usability scale (SUS) questionnaire. To measure the usability level using usability metrics, usability measurement uses aspects of efficiency, effectiveness, learnability, memorability and satisfaction. For aspect satisfaction, use the SUS questionnaire, while efficiency, effectiveness, learnability and memorability aspects are tested by usability. Usability testing is performed on groups of student and prospective student users by providing several tasks, from the test data will be obtained in the form of success of the user working on the task, time spent by the user in working on each task, number of steps and number of clicks and errors made by respondents completing the task. The results of usability testing will be calculated using matric usability. The usability testing, observation, interview and questionnaire methods are used to measure the level of usability on the Faculty of Animal Science website, and explore problems regarding usability. Usability problems found when testing, observation and interviews were then given recommendations according to the usability guidelines. Recommendations are given to improve the website of the Faculty of Animal Science.